HGG-13. BRAIN DISTRIBUTION AND CLEARANCE OF ALISERTIB IS LIMITED BY PGP AND BCRP EFFLUX PUMPS AND DEPENDENT UPON DELIVERY METHOD. (1st June 2021) - Power, Erica; Oh, Juhee; Zhang, Liang; Elmquist, William; Daniels, David
Abstract: Diffuse midline gliomas (DMGs) harboring the H3K27M mutation are highly aggressive, uniformly fatal brain tumors that primarily occur in children. The blood-brain barrier (BBB), including drug efflux pumps, prevent numerous drugs from reaching CNS tumors at cytotoxic concentrations. Alisertib is an aurora kinase inhibitor that was previously identified in a drug screen as a compound of interest. However, its ability to penetrate the BBB is not well established. The goals of this study were two-fold: 1) determine the CNS distribution and clearance rates of alisertib following systemic delivery and if the BBB efflux pumps, Pgp and BCRP, alter distribution and clearance. 2) Compare alisertib distribution and clearance following convection-enhanced delivery to systemic results. WT and Pgp/BCRP knockout mice and Sprague-dawley rats underwent tail vein injection (mice and rats) or convection-enhanced delivery to the brainstem (rats only) of alisertib and sacrificed at 0, 2, 4, 8, 12, 16 and 24hours. The plasma and brain were collected and analyzed for alisertib concentration by HPLC-MS/MS. We found that in both mice and rats, alisertib concentration in the plasma and brain decreased biexponentially. Overall, Alisertib was found to be 3.14% brain penetrant. In Pgp/BCRP knockout mice, alisertib concentration in the plasma and brain decreased biexponentially, but was detected at higher concentration at all time points in the brain compared to WT mice. This resulted in a higher brain penetrance (17.26%). Differences based on anatomical brain region were significant in those rats which received convection-enhanced delivery. Alisertib was found in higher concentration in the pons and cerebellum compared to systemic delivery, but lower concentrations in the cortex and plasma. These results suggest that drug clearance may be a general mechanism limiting efficacy of drugs of interest and should be carefully considered during preclinical evaluation.